An electrochemical assessment of pristine SrCoO3‐δ using the distribution of relaxation times analysis. Issue 4 (16th May 2022) - Ji, Yuexia; Feng, Chuanshuai; Shao, Shande; Li, Xinran; Huang, Xianshan; Cao, Jiafeng
Abstract: Strontium cobalt oxide is an important perovskite‐type material in the research of solid oxide fuel cells (SOFCs), since a great number of derived cathode materials can be obtained through composition modification against SrCoO3‐δ (SCO). In this work, pristine SCO without any additional dopants was synthesized, and its electrochemical properties were evaluated according to the electrochemical impedance spectroscopies (EIS) analyses through the distribution of relaxation times (DRT) method on the symmetrical cells. The undoped SCO displayed low polarization resistances as well as a high oxygen transport ability, even comparable to the famous cathode, Sm0.5 Sr0.5 CoO3‐δ (SSC). Oxygen surface and bulk diffusion were found to be the dominating processes in the oxygen reduction reaction (ORR) of SCO. These results could broaden our knowledge about the ionic transport behavior of SCO‐based perovskite materials.